Structural reinforcement for adaptation of architectural projects in buildings with pre-panels concrete moldings in Brasilia, Brazil - Pantoja, João da Costa (2023)
The purpose of this article was to analyze the structure of an apartment located in a traditional Brasilia’s superblocks, Federal District, where precast concrete panels make up the structural system. Through the rehabilitation solution employing metal plates for reinforcement, it was possible to conceive a new architecture, redefining the layout and expanding the available spaces. Technical visits and sclerometry tests were conducted to thoroughly evaluate the structural condition prior to the interventions. All steps followed the current standards, ensuring the quality and safety of the modifications. The study results conclude that structural reinforcement is an effective solution that enabled the realization of the proposed new architecture, providing greater safety and stability, in addition to enabling the adaptation of the apartment to the needs of the residents.